The effect of the acquisition of parental responsibilities and rights on the realisation of the right to parental care of children born to unmarried parents - Rutgers, Joshua Leon (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLM)--Stellenbosch University, 2020.